Emerging practices supporting diabetes self-management among food insecure adults and families: A scoping review. - Enza Gucciardi; Adalia Yang; Katharine Cohen-Olivenstein; Brittany Parmentier; Jessica Wegener; Vanita Pais (PLoS ONE)
Background Food insecurity undermines a patient's ability to follow diabetes self-management recommendations. Care providers need strategies to direct their support of diabetes management among food insecure patients and families. Objective To identify what emerging practices health care providers can relay to patients or operationalize to best support diabetes self-management among food insecure adults and families. Eligibility criteria Food insecure populations with diabetes (type 1, type 2, prediabetes, gestational diabetes) and provided diabetes management practices specifically for food insecure populations. Only studies in English were considered. In total, 21 articles were reviewed. Sources of evidence Seven databases: Cumulative Index of Nursing and Allied Health Literature, Cochrane Database of Systematic Reviews, Medline, ProQuest Nursing & Allied Health Database, PsychInfo, Scopus, and Web of Science. Results Emerging practices identified through this review include screening for food insecurity as a first step, followed by tailoring nutrition counseling, preventing hypoglycemia through managing medications, referring patients to professional and community resources, building supportive care provider-patient relationships, developing constructive coping strategies, and decreasing tobacco smoking. Conclusion Emerging practices identified in our review include screening for food insecurity, nutrition counselling, tailoring management plans through medication adjustments, referring to local resources, improving care provider-patient relationship, promoting healthy coping strategies, and decreasing tobacco use. These strategies can help care providers better support food insecure populations with diabetes. However, some strategies require further evaluation to enhance understanding of their benefits, particularly in food insecure individuals with gestational and prediabetes, as no studies were identified in these populations. A major limitation of this review is the lack of global representation considering no studies outside of North America satisfied our inclusion criteria, due in part to the English language restriction.